Expedition Vehicles in the Ottoman Miniatures (16th – 18th Centuries) - Ela Taş; Aslıhan Erdoğan (Art-Sanat)
The strides made in military issues as well as the political considerations played major roles in the transformation of the Ottoman state from a small-scale seigniory into a world empire. It is well-known that the conquests made by the mounted troops during the establishment period were sustained with regular armies in parallel to the extension of the state. While the Ottoman state launched expeditions for the sake of imperialistic political considerations, one of the necessities to gain the desired outcome was the necessary equipment for the armies and the successful dispatch of such materials to the battlefields. In this regard, over-land and naval expedition vehicles were utilized during the dispatch of these components. It is also possible to determine the vehicles used by the Ottoman Empire in the expeditions through various miniature manuscripts from this period. As is widely known, miniatures are created to fit within the page margins in order to illuminate the contents of the manuscripts. Thus, the purpose of this study is to discuss the over-land vehicles (e.g., horses, mules, camels, elephants, gun carriages, and chariots) and naval vehicles (e.g., galiots, bastardas, galleons, lighters, and barges), which are mentioned in the miniatures that depict the Ottoman expeditions and express the importance of these events. The vehicles depicted in these manuscripts date back to the 16th–18th centuries, which include the Ottoman expeditions evaluated in this research.